2019
DOI: 10.1186/s13613-019-0502-2
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pulmonary aspergillosis in cirrhotic patients: analysis of a 10-year clinical experience

Abstract: Background Cirrhosis is not recognised as one of the main risk factors of invasive pulmonary aspergillosis (IPA), although its prevalence is increasing. The aim of our study was to identify factors for IPA in such patients with a positive Aspergillus sp. culture in respiratory samples and to evaluate its impact on outcome. Methods We conducted a monocentric retrospective study between January 2005 and December 2015. All cirrhotic patients hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Several studies have been conducted in intensive care units and identified, in the absence of malignancy, HSCT, or solid organ transplantations, the following risk factors for IA: severe chronic obstructive pulmonary disease, steroid therapy, HIV infection, influenza virus infection (especially H1N1), chronic renal replacement therapy, liver failure, near-drowning, prolonged period of mechanical ventilator dependency. 25,[97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Irrespective of these comorbidities, immune paralysis (also called compensatory antiinflammatory response syndrome) induced by severe sepsis can by itself be a risk factor for IA. 114,115 Recently several cases of IA have been reported in patients suffering from severe fever with thrombocytopenia syndrome virus infection, a tick-born disease present in China, Korea, Vietnam, and Japan.…”
Section: Critically Ill Patientsmentioning
confidence: 99%
“…Several studies have been conducted in intensive care units and identified, in the absence of malignancy, HSCT, or solid organ transplantations, the following risk factors for IA: severe chronic obstructive pulmonary disease, steroid therapy, HIV infection, influenza virus infection (especially H1N1), chronic renal replacement therapy, liver failure, near-drowning, prolonged period of mechanical ventilator dependency. 25,[97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Irrespective of these comorbidities, immune paralysis (also called compensatory antiinflammatory response syndrome) induced by severe sepsis can by itself be a risk factor for IA. 114,115 Recently several cases of IA have been reported in patients suffering from severe fever with thrombocytopenia syndrome virus infection, a tick-born disease present in China, Korea, Vietnam, and Japan.…”
Section: Critically Ill Patientsmentioning
confidence: 99%
“…When M. tuberculosis complex was isolated, the diagnosis of pulmonary TB was established. Regarding Aspergillus, cases were classified as CPA according to ESCMID guidelines (Denning et al, 2016) or IPA according to EORTC criteria for immunocompromised patients or Blot modified criteria for critically ill patients (De Pauw et al, 2008;Blot et al, 2012;Ullmann et al, 2018;Levesque et al, 2019). If patients were not included in these definitions, they were classified as colonized (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, they encompass several risk factors, such as a profound immune-dysfunction, prolonged hospitalization, hepatic and extra-hepatic failure(s), indwelling (vascular) catheters, and long-term antibiotic therapies[ 3 , 10 ]. According to available studies on this specific population[ 11 - 16 ], the prevalence of IFD ranges between 1% and 47% (depending on diagnostic criteria and surveillance policies), significantly affecting short-term survival. Nevertheless, heterogeneous selection criteria have not allowed a refinement of risk stratification to date (Table 1 ).…”
Section: Invasive Fungal Disease In Patients Awaiting Ltmentioning
confidence: 99%
“…For the sickest patients who are waiting for a graft, surveillance protocols are mandatory, and antifungal prophylaxis has been advocated in selected cases. For instance, Gustot et al [ 27 ] suggested ICU admission and a baseline MELD score > 24 as factors for considering a prophylaxis against IA in patients with acute alcoholic hepatitis[ 16 , 27 ], but more data are needed before considering it as a standard practice. After diagnosis of IFD, consultation by expert Infectious Disease specialists should be always considered, in order to establish the best targeted antifungal treatment and its length.…”
Section: Invasive Fungal Disease In Patients Awaiting Ltmentioning
confidence: 99%